RANCANG BANGUN METODE PEMBELAJARAN PRAKTIKUM CAD/CAM DENGAN MENGGUNAKAN PERANGKAT LUNAK GRATIS - Redaksi Tim Jurnal (JURNAL POWERPLANT, 2017)
Computer-Aided Design (CAD) is a form of automation that helps designers to improve drawings, specifications, and design-related elements that use special graphical effects and computer program computations. The CAD system is run through PC for 2D design and modeling as well as drafting process, then executed and integrated with CAM (Computer Aided Manufacture) system adapted to CNC (Computer Numeric Control) format to be used. Inventor Software is one of the many CAD software that has many advantages, so it is unthinkable to design the learning method of CAD / CAM Practicum with combination of Autodesk Inventor Software with Hardware Machine CNC Roland EGX-350. The study was conducted on the even semester of the 2015/2016 school year at STT-PLN Jakarta. A more specific object is a student who takes the CAD / CAM course. The end result of the study, shows that from the respondents stated that the design by using AutoCesk AutoCAD Software has a level of convenience 67.62% (Easy). While using AutoDesk Inventor respondents stated having ease of 82.2% (Very Easy).